Chair of Peace: Proposal for Implementation through social networks - García-Noguera, Luis; Dueñas Gaitán, Félix Fernando (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2024)
We sought to review the curricular commitments that the Social Communication and Journalism programs have designed in the implementation of the Chair of Peace, to propose virtual resources that strengthen their appropriation. From the qualitative approach, using focus groups in four universities, it was evident that the implementation of the chair is being worked on with traditional pedagogical resources. The development of the chair is proposed with virtual resources that contribute to the construction of learning. It is concluded that the chair is being developed with face-to-face resources, so it is important to use virtual resources that strengthen its execution.